1933
DOI: 10.1042/bj0270615
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine factors concerned in the control of the ovarian cycle

Abstract: EXPERIMENTAL studies upon the relation of the pituitary gland to the ovarian cycle in mammals involve three principal difficulties: (i) that of removing the pituitary itself without injury to the animal; (ii) the practical impossibility of removing the anterior lobe without removing or damaging the posterior lobe; (iii) the necessity of killing the' test animal, in most cases, to confirm whether injected extracts or transplants have produced ovulation or other changes in the ovaries. None of these objections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1938
1938
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Bellerby (1933) confirmed these observations, and showed that Xenopus injected with alp will lay eggs even outside the normal breeding season. Bellerby (1934) and Shapiro & Zwarenstein (1934) reported on the successful use of Xenopus for the diagnosis of pregnancy.…”
Section: Biological Testssupporting
confidence: 83%
“…Bellerby (1933) confirmed these observations, and showed that Xenopus injected with alp will lay eggs even outside the normal breeding season. Bellerby (1934) and Shapiro & Zwarenstein (1934) reported on the successful use of Xenopus for the diagnosis of pregnancy.…”
Section: Biological Testssupporting
confidence: 83%
“…Extracts of brain and liver prepared by the same method were injected as controls. Pituitary extracts were prepared from sheep anterior lobe according to Bellerby [1933] and extracts of brain and liver were used as controls. Saline suspensions of testes and brain were prepared from ram's tissues as described previously [Schrire & Zwarenstein, 1932, 2].…”
Section: Methodsmentioning
confidence: 99%
“…Xenopus breeding is possible year-round (36,37), with large clutch sizes, up to 2000 eggs per day per frog, and easy in vitro fertilization providing researchers with a large continuous set of developmentally synchronized embryos (38). These embryos develop externally and are therefore easily visible and accessible for microinjection-based genetic manipulations.…”
Section: Advantages Of Xenopus As a Model Organismmentioning
confidence: 99%